Regional wage differentials - does distance matter? - Morten Marott Larsen (European Regional Science Association (ERSA), 2003)
This paper uses econometric methods to analyse causes of regional wage differentials in Denmark for the period1996-1999 and quantifies the importance of spatial proximity. Grouped data sets are used. Two concepts of distance are investigated. The first assumes that there is a positive production externality present in a centre that declines as the distance to the centre increases. Different definitions of a centre are tested. The second distance concept is commuting distance. Both distance measures have the expected sign and are significant, but the effects are small. JEL classification: J31 Key words: Wage differentials, distance, grouped data.
Keywords: 330